Genetic variants associated with serum alanine aminotransferase levels among patients with hepatitis C virus infection: A genome‐wide association study. Issue 9 (3rd June 2021) - Liu, Po‐Chun; Chan, Chi; Huang, Yu‐Han; Chen, Yen‐Ju; Liao, Shu‐Fen; Lin, Yu‐Ju; Huang, Claire; Lu, Sheng‐Nan; Jen, Chin‐Lan; Wang, Li‐Yu; Yang, Hwai‐I; Shen, Chen‐Yang; et al.
Abstract: Information on genetic variants associated with elevated serum alanine aminotransferase (ALT) levels remains limited. A genome‐wide association study was performed to identify single‐nucleotide polymorphisms (SNPs) associated with ALT levels. The ALT‐associated SNP was further evaluated for hepatocellular carcinoma (HCC) risk. A cohort of 892 anti‐HCV seropositive patients was used for genome‐wide SNP array to examine the associations with baseline ALT levels. SNPs <10 −5 were further tested for associations with serial ALT levels then validated in 486 anti‐HCV seropositives. Multinomial logistic regressions were used to estimate odds ratios (ORs) and 95% confidence intervals of SNPs associated with ALT. The SNP was evaluated for HCC risk by using Cox's proportional hazards models. After quality control, 803 participants with 564, 464 SNPs were included in the analysis. Of these, 12 SNPs were associated with ALT ( p < 10 −5 ). Among the participants, 158 (19.7%) had ALT persistently ≤15 U/L, 327 (40.7%) ever >15 U/L but never >45 U/L, and 318 (39.6%) ever >45 U/L during follow‐up. The rs568800 was associated with serial ALT levels, and this was replicated in the external population significantly ( p < .05). The A allele (vs C) of rs568800 was associated with ALT >15 U/L but ≤45 U/L and ALT >45 U/L, with the adjusted ORs of 1.41 (1.11–1.78) and 1.86 (1.34–2.60), respectively. The adjusted HRs for HCC were 2.09 (0.90–4.89) for AC and 2.64 (1.13–6.17) for AA (CC as a reference). In conclusion, the rs568800 was associated with serum ALT levels and HCC risk. Clinical utility should be evaluated among patients who have received antivirals.